Стародавнє піратство: етимологія поняття та формування промислу - Шульга, С. А.; Пінчук, В. І.; Shulha, Svitlana; Pinchuk, Volodymyr (My University, 2017)
У статті розкрито етимологію терміна «піратство». Здійснено спробу визначення етапів еволюції піратського промислу в стародавньому світі, проаналізовано тактику піратів. Розкрито основні цілі піратів, показано їхні стосунки з правителями.The article explores the evolution of piracy in the ancient world. The authors consider the modifications of the term «pirate» and determine the chronological framework of the selected stages of piracy development. It is stated that piracy emerged simultaneously with the sea trade when there was little difference between a merchant and pirate life. The most active in the pirate trade in the East were the Phoenicians, Cretans and Egyptians. The next stage in the piracy development was the period of Phoenician and Greek colonization when the expeditions were of state and private character. In 5-1 BC piracy acquired an organized character and was against the state interests in the Mediterranean.
Ancient Piracy: the Etymology of the Concept and the Formation of the Trade
Keywords: піратство; пірат; торгівля; колонізація; піратський промисел; античність; Стародавній Схід; piracy; pirate; trade; colonization; piracy trade; Antiquity; the Ancient East